PICTURE AS A DIAGNOSTIC TREATMENT OF HUMANSOMATIC IMPACTS - Sargsyan , S.F. (Modern Psychology, 2019)
We live in the era of the popularity of integrative psychotherapy, and in different areas suggesting an integrated approach. The article discusses the problem of the interaction of art therapy and body-oriented psychotherapy, taking into account the diagnostic capabilities of the picture. Drawing has come a long way and is an auxiliary method during therapy. Based on our many years of art-therapeutic work, we propose a projection-drawing method, during which an attempt is made to an integrative approach.
Keywords: art therapy, integrative background, picture, projection, assessment.